2017
DOI: 10.1136/heartjnl-2017-311978
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of persistent pulmonary hypertension following transcatheter aortic valve replacement

Abstract: Objectives To determine the prevalence and factors associated with persistent pulmonary hypertension (PH) following transcatheter aortic valve replacement (TAVR) and its relationship with long-term mortality. Methods Consecutive patients who underwent TAVR from July 2011 through January 2016 were studied. The prevalence of baseline PH (mean pulmonary artery pressure ≥25 mm Hg on right heart catheterisation) and the prevalence and the predictors of persistent≥moderate PH (pulmonary artery systolic pressure (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 21 publications
2
47
0
1
Order By: Relevance
“…3 There is relatively recent evidence that in patients with severe AS, PH often persists after AVR, 5,6 and that post-AVR PH is a more important prognostic predictor than pre-AVR PH. 5 Since this information is derived from echocardiographic studies, the detailed haemodynamic pattern prior and post AVR of these patients remains unknown. We hypothesize that these patients with persistent PH after AVR may have had CpcPH beforehand but this remains to be shown in future studies.…”
Section: Prognostic Importance Of Combined Pre-and Post-capillary Pulmentioning
confidence: 99%
See 1 more Smart Citation
“…3 There is relatively recent evidence that in patients with severe AS, PH often persists after AVR, 5,6 and that post-AVR PH is a more important prognostic predictor than pre-AVR PH. 5 Since this information is derived from echocardiographic studies, the detailed haemodynamic pattern prior and post AVR of these patients remains unknown. We hypothesize that these patients with persistent PH after AVR may have had CpcPH beforehand but this remains to be shown in future studies.…”
Section: Prognostic Importance Of Combined Pre-and Post-capillary Pulmentioning
confidence: 99%
“…In patients with severe aortic stenosis (AS), PH is frequent and a marker of poor prognosis . However, the majority of data on PH in AS patients are derived from echocardiography studies, where systolic pulmonary artery pressure (PAP) is estimated by measurement of peak tricuspid regurgitation velocity. This together with indirect signs of PH gives a reasonable estimate of the probability of significant PH 7 but does not allow assessing the underlying haemodynamic mechanisms of PH in detail …”
Section: Introductionmentioning
confidence: 99%
“…A study of 433 patients who underwent pre-interventional invasive hemodynamic assessment showed that pre-capillary PH and CpcPH (defined as DPG ≥ 7 mmHg), but not IpcPH, were associated with a significantly higher 1-year mortality after TAVI [51]. Moreover, persistence of PH post-TAVI is common, and even moderate PH is associated with higher all-cause mortality [52].…”
Section: Aortic Valve Stenosismentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Pulmonary hypertension is a sign of advanced cardiac damage due to severity of AS according to damage stages 3 and 4 as described by Genereux et al 12 Previous studies in patients with PH showed an increased mortality after aortic valve replacement (AVR) and PH to be a marker for poor prognosis. 6,7,[9][10][11]13,14 Therefore, assessment of PH is important for risk stratification, with PH being one of the components of the logistic EuroSCORE and the EuroSCORE II. Especially, in the field of AVR, the presence of PH is import for risk stratification and provides information for the "heart team" to evaluate whether to undergo surgical (SAVR) or transcatheter AVR (TAVR).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, in the field of AVR, the presence of PH is import for risk stratification and provides information for the "heart team" to evaluate whether to undergo surgical (SAVR) or transcatheter AVR (TAVR). 6,7,[9][10][11]13,14 Pulmonary hypertension is defined by a mean pulmonary artery pressure (MPAP) ≥25 mm Hg. Although right heart catheterization (RHC) is the "gold standard" for direct measurements of pulmonary artery pressures according to ESC/ERS guidelines, 15 it is an invasive tool and accompanied by possible complications.…”
Section: Introductionmentioning
confidence: 99%